(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
The relationship between school history and citizenship education goes back to the presence of this subject at the beginning of obligatory school. However, the senses attributed both to citizenship training in school have not been univocal, nor have the senses of teaching history. In this paper we propose to investigate the relationship between the senses that history teachers attribute to the teaching of history and citizenship formation in secondary school and the programming they carry out in order to bring their teaching proposal to the classroom. For this we will identify the conceptions that teachers have about citizenship education, to address the relationship that can be established with the teaching of the history they make through the selection of contents and the historical stories that appear in the materials they use. Through qualitative methods we will collect and analyze curricular materials used by teachers in their history classes, as well as books on topics and programs. We will also conduct interviews with history teachers. We consider them significant from the adopted perspective since through them we will inquire about the criteria of selection of contents and historical stories that the teachers make for their classes in relation to the purposes that they attribute to the teaching of history.